Territorial Innovation in Less Developed Regions
XXIII, 305 p. 43 illus., 34 illus. in color.
Keywords: This book examines the roles of communities in the general framework of territorial innovation, particularly in the context of less developed regions. With a specific focus on Portugal, it offers conceptual improvements that will be of use to other European regions. The book will appeal to scholars and students of regional governance and politics, from public administration to economics, sociology, geography and political science, as well as to practitioners. Filipe Teles is Pro-Rector for Regional Development and Urban Policies at the University of Aveiro. Fernando Ramos is Professor of Communication Sciences and Technologies at the University of Aveiro. Carlos Rodrigues is Associate Professor and Head of the Department of Social, Political and Territorial Sciences at the University of Aveiro. Anabela Botelho is Professor of Economics at the University of Aveiro. .